(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to determine the Influence of Intellectual Capital and Good Corporate Governance on the Financial Performance of Manufacturing Companies in the Consumer Goods Subsector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Intellectual Capital is measured using the Value Added Intellectual Capital (VAIC) model which has three components (physical capital, human capital, and structural capital). Good Corporate Governance is measured by Institutional Ownership, Managerial Ownership, Board of Commissioners, and Audit Committee. while financial performance is measured by return on assets (ROA). This type of research is a quantitative research and the type of data used in this study uses secondary data in the form of documents taken from the annual report in 2019- 2023. The data collection technique uses purposive sampling in sample selection. The sample obtained from this study amounted to 26 companies from 76 manufacturing companies listed on the Indonesia Stock Exchange. The analysis method in this study is panel data regression analysis, using Eviews 12 software. The results of this study show that the independent variable of Intellectual Capital measured using the Value Added Intellectual Capital (VAIC) model has an effect on financial performance measured by Return On Asset (ROA), while the variable of good corporate governance measured by institutional ownership has no effect on financial performance measured by Return On Asset (ROA), managerial ownership has no effect on financial performance measured by Return On Asset (ROA). On Asset (ROA), the board of commissioners has an effect on financial performance measured by Return On Asset (ROA) and the audit committee has no effect on financial performance as measured by Return On Asset (ROA).